Preventing aspartimide formation in Fmoc SPPS of Asp‐Gly containing peptides — practical aspects of new trialkylcarbinol based protecting groups. (11th January 2016) - Behrendt, Raymond; Huber, Simon; White, Peter
Abstract: In our efforts to develop a universal solution to the problem of aspartimide formation in Fmoc SPPS, we investigated the application of our new β ‐trialkylmethyl protected aspartic acid building blocks to the synthesis of peptides containing the Asp‐Gly motif. The N α ‐Fmoc aspartic acid β ‐tri‐(ethyl/propyl/butyl)methyl esters were used in the synthesis of the classic model peptide scorpion toxin II (VKDGYI), and their effectiveness in minimising aspartimide formation during extended piperidine treatments was evaluated. Furthermore, we compared their efficacy against that of the commonly used approach of adding acids to the Fmoc deprotection solution. Finally, we applied our aspartic acid building blocks to the stepwise Fmoc SPPS of teduglutide, a human GLP‐2 analogue, whose synthesis is made challenging by extensive aspartimide formation. In all experiments, our approach led to almost complete reduction of aspartimide formation with accompanied suppression of aspartic acid epimerisation. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The notoriously aspartimide prone Asp‐Gly sequence motif was efficiently protected from aspartimide formation by the new β ‐trialkylmethyl aspartic acid compounds in the scorpion toxin II fragment. Applied to routine Fmoc SPPS these compounds enabled the preparation of (Gly2)‐GLP‐2 (teduglutide), which should support the rapid development of new GLP‐2 analogs.